2022
DOI: 10.3390/ijerph19063581
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Tooth Width Measurements Delivered by the Clin-Check Pro 6.0 Software on Digital Casts: A Cross-Sectional Study

Abstract: The purpose of this study was to assess the accuracy and reliability of tooth width measurements and Bolton Indices delivered by the Clin-Check Pro 6.0 software (Align Technology, San José, CA, USA). Fifty-four plaster casts were selected and measured with a manual calliper by a trained and calibrated observer. The data gathered were compared with those delivered by the software on the corresponding fifty-four virtual casts. The method reliability of the software was assessed by comparing the measurements perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Notably, a trend of greater underestimation was observed, particularly in posterior teeth. In contrast, Adobes et al [18] reported the opposite, with ClinCheck Pro tending to display larger widths. Soto-Alvarez et al [19] and Rajshekar et al [20] found substantial agreement with no statistically significant differences between the cast and digital models.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, a trend of greater underestimation was observed, particularly in posterior teeth. In contrast, Adobes et al [18] reported the opposite, with ClinCheck Pro tending to display larger widths. Soto-Alvarez et al [19] and Rajshekar et al [20] found substantial agreement with no statistically significant differences between the cast and digital models.…”
Section: Discussionmentioning
confidence: 92%
“…In the field of dentistry, the digital workflow is increasing and offering viable impression, design, and manufacturing protocols for prosthetic dentistry [41]. However, multiple different scanners and types of software are available, and features such as trueness, accuracy, and precision are important to comprehend and to be evaluated in order to obtain the proper information and possible limitations about the system used [42].…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after the initial measurements, the same student repeated crowding analysis on each model in a random order. The decision to measure crowding on physical rather than digital models was based on variation in study findings, with some reporting digital measurements to be larger than manual measurements, and others finding them to be smaller (Adobes et al, 2022, Naidu et al, 2013, Santoro et al, 2003, Shailendran et al, 2021. The assessor was blinded to all records and patient identifiers during the measurement process.…”
Section: Crowding Analysismentioning
confidence: 99%